Reduction of pentavalent and trivalent arsenic by TiO2- photocatalysis: an innovative way for arsenic removal - Litter, Marta Irene; Levy, Ivana Karina; Quici, Natalia; Mizrahi, Martin Daniel; Ruano Sandoval, Gustavo Daniel; Zampieri, Guillermo Enrique; Requejo, Felix Gregorio (CRC Press - Taylor & Francis Group, 2014)
Fil: Litter, Marta Irene. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Seguridad Nuclear y Ambiente. Gerencia de Química (CAC); Argentina